Energy-Efficient Sector-Based Routing in 3D Wireless Sensor Networks Using Midpoint-Aware Cluster Head Selection - Nirwana Haidar Hari; Ahmad Khairul Umam; Lusiana Agustien (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2026)
Energy efficiency is a key concern in three-dimensional Wireless Sensor Networks (3D WSNs), where irregular node distribution can shorten network lifetime. This study introduces a novel sector-based clustering protocol that partitions the sensing field azimuthally and selects Cluster Heads (CHs) based on residual energy and distance to each sector’s geometric midpoint. The core innovation lies in an adaptive threshold formula that incorporates both energy and spatial distance, enabling fairer CH rotation and better intra-cluster communication. This approach ensures more balanced energy depletion and improved load distribution. Simulations in a 3D environment showed that the proposed protocol outperformed LEACH-Classic, LEACH-GA, and LEACH-KMeans in FND, HND, LND, residual energy, and throughput. Notably, it improves FND by up to 59.2% compared to LEACH and increases throughput by 37.8%, confirming the benefits of azimuth-based clustering and midpoint-aware CH selection.